Introduction: Reuse and Intertextuality in the Context of Buddhist Texts - Freschi, Elisa; Cantwell, Cathy (Buddhist Studies Review, 2017)
The bulk of the present volume focuses on the reuse of Buddhist texts. The Introduction gives some background to the topic of textual reuse in general and discusses the reasons for undertaking the analysis of textual reuse within Buddhist texts. It then elaborates on the extent of its pervasiveness within Buddhist literature through the example of Tibetan ritual texts. Lastly, it takes stock of the articles on text-reuse and discusses some general lines of interpretation of the phenomenon of textual reuse in Buddhism, highlighting the importance of the genre over that of the time and language of composition. Thus, philosophical or technical texts tend to quote explicitly, whereas ritual texts see the predominance of the conveyed message over the transparency of the transmission so that reuse is mostly silent. Religious texts of various forms come in between these two extremes.